Arousal Modulates Auditory Attention and Awareness: Insights from Sleep, Sedation, and Disorders of Consciousness - Chennu, Srivas; Bekinschtein, Tristan A. (Frontiers in Psychology, 2012)
The interplay between top-down, bottom-up attention and consciousness is frequently tested in altered states of consciousness, including transitions between stages of sleep and sedation, and in pathological disorders of consciousness (the vegetative and minimally conscious states; VS and MCS). One of the most widely used tasks to assess cognitive processing in this context is the auditory oddball paradigm, where an infrequent change in a sequence of sounds elicits, in awake subjects, a characteristic EEG event-related potential (ERP) called the mismatch negativity (MMN), followed by the classic P300 wave. The latter is further separable into the slightly earlier, anterior P3a and the later, posterior P3b, linked to bottom-up and top-down attention, respectively. We discuss here the putative dissociations between attention and awareness in disorders of consciousness, sedation and sleep, bearing in mind the recently emerging evidence from healthy volunteers and patients. These findings highlight the neurophysiological and cognitive parallels (and differences) across these three distinct variations in levels of consciousness, and inform the theoretical framework for interpreting the role of attention therein.